2007
DOI: 10.1080/02673030701474792
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Neighborhood-Type Mobility: Examining Differences between Blacks and Whites

Abstract: Using sibling data from the Panel Study of Income Dynamics linked with US Census data, this paper examines the intergenerational nature of neighborhood quality. It is hypothesized that the quality of where one resides as an adult is a function of one's childhood neighborhood through the conditioning and constraining of adult residential choice. Further, it is posited that this relationship varies by race and is stronger for those living in the most disadvantaged neighborhoods, especially blacks. Descriptively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 36 publications
3
60
0
Order By: Relevance
“…These authors have found that even in adulthood, up to almost two decades after leaving the parental home, parental neighbourhood characteristics are a strong predictor for the independent neighbourhood history of their children and for the length of their exposure to deprived neighbourhoods over the life course. Furthermore, for ethnic minority groups, these patterns were stronger than for majority groups (Hedman et al, 2013;Sharkey and Elwert, 2011;van Ham et al, 2014;Vartanian et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…These authors have found that even in adulthood, up to almost two decades after leaving the parental home, parental neighbourhood characteristics are a strong predictor for the independent neighbourhood history of their children and for the length of their exposure to deprived neighbourhoods over the life course. Furthermore, for ethnic minority groups, these patterns were stronger than for majority groups (Hedman et al, 2013;Sharkey and Elwert, 2011;van Ham et al, 2014;Vartanian et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…The neighbourhood, however, as a potential spatial dimension to such intergenerational transmission patterns, has largely been left out of consideration. To our knowledge, there are only a few studies that have examined parent-to-child transfer of disadvantageous neighbourhood characteristics, conducted on Swedish and United States' national data (Hedman et al, 2013;Sharkey and Elwert, 2011;van Ham et al, 2014;Vartanian et al, 2007). These authors have found that even in adulthood, up to almost two decades after leaving the parental home, parental neighbourhood characteristics are a strong predictor for the independent neighbourhood history of their children and for the length of their exposure to deprived neighbourhoods over the life course.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have used the data to examine neighborhood effects on child, adolescent, and young adult development ( (Sharkey 2008), the inter-generational transmission of neighborhood context (Dawkins 2005a;Sharkey 2008;Solon et al 2000), and fertility behavior South and Crowder 2010;South 1999South , 2001aSouth , 2001b. Because of its oversample of African American families, the data have been used to examine levels and trends in racial equality in neighborhood economic status and migration (Sharkey 2008;Dawkins 2005bDawkins , 2006Freeman 2005aFreeman , 2005bFreeman , 2008South and Crowder, 2005;Timberlake 2007;White et al 2005;Vartanian et al 2007;Crowder and South 2005).…”
Section: Effects Of Neighborhoods Over Timementioning
confidence: 99%
“…The data have been used to examine correlations across generations in health (Davis et al 2008;Valerio et al 2009), socioeconomic status (Charles and Hurst 2003;Eberharter 2008;Gouskova et al 2010;Lee and Solon 2009;Mayer and Lopoo 2005;Solon 1992;Vartanian et al 2007), and philanthropic behavior (Wilhelm 2008). In fact, because of the length of the panel, PSID is now being used to estimate changes over time in the intergenerational transmission of economic status (Lee and Solon 2009;Mayer and Lopoo 2008).…”
Section: Socio-economic Outcomes Across and Within Generations Of Thementioning
confidence: 99%